High removal efficacy of Hg(II) and MeHg(II) ions from aqueous solution by organoalkoxysilane-grafted lignocellulosic waste biomass - Saman, N. (Elsevier Ltd, 2017)
An effective organoalkoxysilanes-grafted lignocellulosic waste biomass (OS-LWB) adsorbent aiming for high removal towards inorganic and organic mercury (Hg(II) and MeHg(II)) ions was prepared. Organoalkoxysilanes (OS) namely mercaptoproyltriethoxylsilane (MPTES), aminopropyltriethoxylsilane (APTES), aminoethylaminopropyltriethoxylsilane (AEPTES), bis(triethoxysilylpropyl) tetrasulfide (BTESPT), methacrylopropyltrimethoxylsilane (MPS) and ureidopropyltriethoxylsilane (URS) were grafted onto the LWB using the same conditions. The MPTES grafted lignocellulosic waste biomass (MPTES-LWB) showed the highest adsorption capacity towards both mercury ions. The adsorption behavior of inorganic and organic mercury ions (Hg(II) and MeHg(II)) in batch adsorption studies shows that it was independent with pH of the solutions and dependent on initial concentration, temperature and contact time. The maximum adsorption capacity of Hg(II) was greater than MeHg(II) which respectively followed the Temkin and Langmuir models. The kinetic data analysis showed that the adsorptions of Hg(II) and MeHg(II) onto MPTES-LWB were respectively controlled by the physical process of film diffusion and the chemical process of physisorption interactions. The overall mechanism of Hg(II) and MeHg(II) adsorption was a combination of diffusion and chemical interaction mechanisms. Regeneration results were very encouraging especially for the Hg(II); this therefore further demonstrated the potential application of organosilane-grafted lignocellulosic waste biomass as low-cost adsorbents for mercury removal process. © 2016 Elsevier Ltd